The Influence of Translation Techniques on the Accuracy of Interpretation of Little Women by Louisa May Alcott - Suryadi, Fidela Shaumi; Azzakhro, Devika Fatimah; Fauzan, Dheriyan; Ardiansya, Erlan Aditya (Journal of English Education Forum (JEEF), 2024)
This study analyzes the influence of translation techniques on the accuracy of the interpretation of Louisa May Alcott's novel "Little Women". The three translation techniques analyzed are literal translation, idiomatic translation, and dynamic equivalence. This study uses a qualitative method with a content analysis approach from the novel “Little Women”. This method was chosen to explore in depth how translation techniques affect the accuracy of interpretation in the translated novel. These findings emphasize the importance of choosing the right translation technique to maintain the integrity of literary interpretation. This study also highlights the importance of considering cultural and social contexts in the process of translating literary texts. It was found that a deep understanding of the author's original culture is essential to produce an accurate and meaningful translation. In addition, this study recommends that translators have strong linguistic and literary skills to be able to transfer the nuances and meanings contained in the original text into their translations. The findings of this study can be a valuable guide for translators and researchers in understanding the complexity of translation techniques and their impact on the interpretation of literary texts.